Catalytic Oxidation of Alcohol to Carboxylic Acid with a Hydrophobic Cobalt Catalyst in Hydrocarbon Solvent. Issue 18 (16th August 2017) - Shi, Song; Liu, Meng; Zhao, Li; Wang, Min; Chen, Chen; Gao, Jin; Xu, Jie
Abstract: A hydrophobic cobalt catalyst was synthesized and proved to be effective in alcohol oxidation under the assistance of hydrocarbon solvent with oxygen as the terminal oxidant. A series of catalysts with different water contact angles was applied to investigate the hydrophobic effect. Further insight into the reaction process was gained by reaction kinetics, isotopic effect, etc. It showed that the hydrocarbon solvent participated in the alcohol oxidation, and with the aid of the in situ generated free radicals, the α‐C−H bond was smoothly activated and the alcohol was converted to carbonyl compounds. The hydrophobic effect promoted the alcohol oxidation by affecting the solvent oxidation. Abstract : Hydrophobic catalyst : An efficient method for alcohol oxidation was developed through the activation of the α‐C−H bond by the in situ generated free radicals of hydrocarbon oxidation. A series of catalysts with different water contact angles was applied to investigate the hydrophobic effect of the catalyst.